The relationship between employee engagement and human resource practices on employee retention - Suthashinni, Raju (2021)
The main objective of this study is to investigate the relationship between employee engagement and human resources practices (Recruitment and selection, training and development, compensation and performance management) on employee retention. To attain the objectives, the quantitative method was used and data were collected through questionnaires and google form method. A total of 201 questionnaires were received and used for further analysis. The data were analysed using Pearson correlation and standard multiple regression. The findings exhibited that, there were relationship between employee engagement and human resource practices on employee retention. All the dimensions of human resource practices namely recruitment and selection, training and development, compensation and performance management were correlated with employee retention. In conclusion, it is observed that human resource practices and employee engagement have influence on the employee retention. This shows that employers need to develop a proper and well-structured human resource management policies in attaining high work engagement level and retention among the auditors.